2009
DOI: 10.1002/ijc.24257
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: Overexpression of Aurora A by loss of CHFR gene expression increases the growth and survival of HTLV‐1‐infected T cells through enhanced NF‐κB activity

Abstract: Retraction: The following article has been retracted through agreement between the first author and several coauthors, the journal Editor‐in‐Chief, Peter Lichter, and John Wiley & Sons, Ltd.: Tomita M, Toyota M, Ishikawa C, Nakazato T, Okudaira T, Matsuda T, Uchihara JN, Taira N, Ohshiro K, Senba M, Tanaka Y, Ohshima K, Saya H, Tokino T, Mori N. (2009). Overexpression of Aurora A by loss of CHFR gene expression increases the growth and survival of HTLV‐1‐infected T cells through enhanced NF‐kappaB activity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 44 publications
(65 reference statements)
2
17
1
Order By: Relevance
“…15 We reported previously that a pan-Aurora kinase inhibitor, which inhibits both Aurora A and Aurora B kinases, suppresses cell growth of HTLV-1-infected T-cell lines and primary ATL cells by inducing apoptosis through inhibition of nuclear factor-kappa B (NF-jB) activity. 16 In our study, we used AZD1152-HQPA in vitro to evaluate the effects of specific inhibition of Aurora B in HTLV-1-infected T-cell lines.…”
mentioning
confidence: 99%
“…15 We reported previously that a pan-Aurora kinase inhibitor, which inhibits both Aurora A and Aurora B kinases, suppresses cell growth of HTLV-1-infected T-cell lines and primary ATL cells by inducing apoptosis through inhibition of nuclear factor-kappa B (NF-jB) activity. 16 In our study, we used AZD1152-HQPA in vitro to evaluate the effects of specific inhibition of Aurora B in HTLV-1-infected T-cell lines.…”
mentioning
confidence: 99%
“…However, no evidence showing CHFR ubiquitination of Aurora A directly leading to instability was demonstrated (140). Nonetheless, several other studies showed that downregulation or loss of CHFR in cells is closely associated with elevated Aurora A expression (89,98,125). However, CHFR overexpression in HCT116 cells did not destabilize Aurora A (116).…”
Section: Molecular Characterization Of Chfrmentioning
confidence: 98%
“…Aurora A is overexpressed in HTLV-1-infected and ATLL cells. siRNA knockdown experiments and chemical inhibition of Aurora A has been reported to lead to growth suppression in HTLV-1-infected cell [65] . The ubiquitin ligase CHFR regulates the turnover of Aurora A, and in infected cells CHFR level is reduced by methylation and subsequent silencing of its promoter [65] .…”
Section: Cell Cyclementioning
confidence: 99%
“…siRNA knockdown experiments and chemical inhibition of Aurora A has been reported to lead to growth suppression in HTLV-1-infected cell [65] . The ubiquitin ligase CHFR regulates the turnover of Aurora A, and in infected cells CHFR level is reduced by methylation and subsequent silencing of its promoter [65] . Aurora B is overexpressed in HTLV-1-infected cells and its specific inhibition induces apoptosis only in HTLV-1-infected cells compared to non-infected, through overexpression of p21/Waf1 and p53 [66] .…”
Section: Cell Cyclementioning
confidence: 99%